Comparison of Two Urinary Antigen Tests for Establishment of Pneumococcal Etiology of Adult Community-Acquired Pneumonia - Strålin, Kristoffer (American Society for Microbiology, 2004)
The Binax NOW immunochromatographic test (ICT) detecting the pneumococcal C polysaccharide and a serotype-specific latex agglutination (LA) test detecting 23 pneumococcal capsular antigens were evaluated for establishing pneumococcal etiology in community-acquired pneumonia (CAP) by use of nonconcentrated urine. ICT was considered to be strongly positive for result lines at least as intense as the control line and weakly positive for less intense result lines. When 215 adult CAP patients were tested, strong ICT, weak ICT, and LA positivity were found in 28, 24, and 16 patients, respectively; of these patients, 13 (46%), 6 (25%), and 13 (81%), respectively, had pneumococcal bacteremia and 27 (96%), 17 (71%), and 15 (94%), respectively, had Streptococcus pneumoniae isolated from blood, sputum, and/or nasopharynx. Among 108 controls tested, 2 (1.9%) were weakly ICT positive. When weak positivity was considered negative, the sensitivity of ICT decreased from 79% (19 of 24) to 54% (13 of 24), while the specificity increased from 83% (158 of 191) to 92% (176 of 191); no controls were false positive. The sensitivity and specificity of LA were 54% (13 of 24) and 98% (188 of 191), respectively. Eight of nine LA serotypes corresponded to culture serotypes. In conclusion, using nonconcentrated urine and dividing ICT-positive results into strongly and weakly positive results is a suitable way of performing ICT. While weak ICT positivity should be interpreted with caution, strong ICT positivity and LA positivity should be considered supportive of pneumococcal etiology in adult CAP. As such, these assays might have implications for antibiotic use in CAP. LA has promising potential for pneumococcal serotyping, although further evaluation is required.